(untitled) (European Journal of Formal Sciences and Engineering, 2023)
Border Gateway Protocol (BGP) is the actual routing inter-domain protocol in the Internet. The size, heterogenity and changebility that characterize todays Internet put always increasing requirements on BGP performance. The research community has already reported the unwanted characteristics of BGP like low integrity and slow convergence through theoretichal analyzes andd empirical measurements. Simulations allow for more realistic and flexible experiments than the theoretichal approach and also lower costs than the measurements in real life environments. The first part of this work describe theoretically characteristics and problems related to BGP nd also expectations of the today Internet users to real time applications (like VoIP). The second part concentrates in identifying and implementing of the elements for creating an integrated simulation environment for evaluating dhe effects of slowconvergence of BGP in these applications. At last it is evaluated the created environement through some small scale simmulations that try to model the now days Internet Structure.